Impact of heterogeneous nuclear ribonucleoprotein A/B subtype overexpression on the expression of cancer stem cell markers CD133 and CD44 and cellular proliferation capacity: Impact of hnRNPA/B on CD133 and CD44 - Wang, Meng; Wang, Xian; Cui, Yaping; Wen, Xing (Cellular and Molecular Biology, 2023)
The occurrence and progression of intestinal cancer are complex, multifactorial processes in which tumor stem cells are believed to play a crucial role. An in-depth understanding of their molecular mechanisms holds imperative clinical significance for improving intestinal cancer treatment. HT-29 and HCT116intestinal cancer cell lines were utilized as research models. The experimental group (group E) and control group (group C) were established by transfecting the hnRNPA1 subtype and empty vector, respectively. The expression (EP) levels of hnRNPA1 and changes in Wnt/β-catenin signaling-related markers were evaluated using techniques such as RNA extraction, reverse transcription reactions, real-time quantitative PCR (RT qPCR), and protein extraction. The EP of tumor stem cell markers CD133 and CD44 was assessed using immunohistochemistry. Additionally, cell invasion assays, scratch assays, and cell counting kit-8 (CCK-8) proliferation assays were conducted. Furthermore, a mouse tumor model was established to observe the growth of tumors in both groups. overexpression (OP) of hnRNPA1 in group E greatly increased the protein EP levels of β-catenin, Axin2, and Cyclin D1 and exhibited a higher positivity rate for CD133 and CD44. The invasive, migratory, and proliferative abilities of cells in group E were notably enhanced, and tumor growth was observably faster versus group C. OP of hnRNPA1 was closely associated with the activation of Wnt/β-catenin signaling and promoted the proliferation and invasive capacity of tumor cells. hnRNPA1 played an imperative role in intestinal cancer stem cells.